Unity in Diversity: Perbandingan Mode Naratif Apokaliptik dalam Teks Mosalaparwa dan Cariyos Dajal - Nurmalia Habibah (Manuskripta, 2023)
The dynamics of the development of Javanese literature show a spirit of tolerance and welcoming towards outside elements without neglecting the original ones. This is contradictory when juxtaposed with the fact that there are currently widespread phenomena of radicalism and intolerance. Responding to these social issues, this writing at a larger level will show that cultural heritage surprisingly take off differences that trigger religion-based conflicts and shows the existence of the essence of unity in diversity through the uncovering of the meaning of literary works. At a more specific level, this paper aims to reveal the universality of the Javanese view of the eschatological crisis that ends in the Judgment Day event through a close reading of a comparison of the apocalyptic narrative mode in the text of Old Javanese Mosalaparwa and Cariyos Dajal. After examining the two narrative texts in the realm of Javanese literature, there are narrative sections that form the structure of the text and reflect apocalyptic characteristics so that these local religious texts can be placed in the category of literary texts with apocalyptic narrative mode. When looking at the end of the story, referring to the classification of the apocalyptic genre according to Collins (2014), the Mosalaparwa text belongs to the historical apocalypses sub-type and the Cariyos Dajal text pertains to the apocalypses with heavenly journeys. --- Dinamika perkembangan sastra Jawa memperlihatkan adanya jiwa toleran dan welcoming terhadap unsur dari luar tanpa abai terhadap unsur asli. Hal ini bertolak belakang apabila disandingkan dengan fakta adanya fenomena radikalisme dan intoleransi yang marak saat ini. Merespon isu sosial tersebut, tulisan ini pada tataran yang lebih besar akan menunjukkan bahwa warisan budaya justru menanggalkan perbedaan yang menjadi pemicu konflik berbasis agama dan menunjukkan adanya esensi kebhinnekatunggalikaan melalui pengungkapan makna karya sastra. Pada tataran yang lebih khusus tulisan ini bertujuan untuk mengungkap universalitas pandangan masyarakat Jawa terhadap krisis eskatologis yang berujung pada peristiwa kiamat melalui close reading terhadap perbandingan mode naratif apokaliptik dalam teks Mosalaparwa Jawa Kuna dan Cariyos Dajal. Setelah kedua teks kisah hari akhir dalam ranah sastra Jawa tersebut dicermati, terdapat bagian-bagian naratif yang membentuk struktur teks dan mencerminkan karakteristik apokaliptik sehingga teks-teks religius lokal itu dapat ditempatkan dalam kategori teks sastra bermode naratif apokaliptik. Apabila melihat akhir ceritanya, maka merujuk pada klasifikasi genre apokaliptik menurut Collins (2014), teks Mosalaparwa termasuk ke dalam sub-tipe historical apocalypses dan teks Cariyos Dajal ke dalam apocalypses with heavenly journeys.